NAVIGATING EAST AND WEST: LANGUAGE TEACHERS AS INTERCULTURAL MEDIATORS - Michelle Kohler (University of Muhammadiyah Purwokerto, 2012)
The move in recent times from a native speaker norm as the ultimate goal of language learning to a bilingual speaker norm requires a new understanding of the role of the language teacher. Rather than transmitter of knowledge or facilitator of learning, the language teacher is a mediator of language and culture, standing between students' language(s) and culture(s) and the target language and culture. This role presents a number of challenges for language teachers as they consider the implications for their practice and for their own linguistic and cultural identities. Using examples from teachers of Indonesian as a second language in Australian schools, this paper examines how teachers of languages must navigate the local and the additional language and culture with their students in practice. Keywords: Mediation, intercultural, language teaching